SISTEM PENANGANAN PASCAPANEN TANAMAN PADI DI KECAMATAN CIRUAS KABUPATEN SERANG - Husniyyah, Erlinda Alya Husniyyah; Vega Yoesepa Pamela; Fitria Riany Eris (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
Rice is a staple crop with a high level of consumption in Indonesia. Rice paddy areas in Indonesia are vast and spread evenly across Java Island, especially Banten Province. Ciruas as one of the sub-districts with a large rice field area makes this area the center of rice production in Banten Province.  This research aims to find out the post-harvest handling applied to rice plants in Ciruas Sub-district. This research was conducted in rice fields and agricultural instruments in Singamerta Village, Ciruas Subdistrict, Serang Regency through observation and interviews with farmers who are members of the Singamerta Village Farmer Partner Group. Rice plants in the rice fields of Ciruas Subdistrict are harvested when 90-95% of the rice panicles are yellow to golden yellow, then threshed using a power tresher machine and dried conventionally using solar heat. The results of the drying are then milled into rice and packed in white plastic sacks with a capacity of 50 kg of rice and stored temporarily at BPSIP Banten or directly submitted to Bulog Singamerta. Pest and disease control of rice plants is carried out by applying herbicides, insecticides, and special medicines.